2019
DOI: 10.1103/physrevx.9.021016
|View full text |Cite
|
Sign up to set email alerts
|

Bright On-Demand Source of Antibunched Microwave Photons Based on Inelastic Cooper Pair Tunneling

Abstract: The ability to generate single photons is not only an ubiquitous tool for scientific exploration with applications ranging from spectroscopy and metrology 1,2 to quantum computing 3 , but also an important proof of the underlying quantum nature of a physical process 4 . In the microwave regime, emission of anti-bunched radiation has so far relied on coherent control of Josephson qubits 5-8 , where precisely calibrated microwave pulses are needed, and the achievable bandwidth is limited by the anharmonicity of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 42 publications
2
43
1
Order By: Relevance
“…This is clearly not the case in our experiments. In a totally independent experiment with a different objective, Grimm and co-workers [27] have recently observed that a Josephson junction with E J /E C 0.3 in series with a 32 kΩ resistance (R Q /R 0.2) allows a supercurrent flow. We consider their observation backs our results.…”
mentioning
confidence: 99%
“…This is clearly not the case in our experiments. In a totally independent experiment with a different objective, Grimm and co-workers [27] have recently observed that a Josephson junction with E J /E C 0.3 in series with a 32 kΩ resistance (R Q /R 0.2) allows a supercurrent flow. We consider their observation backs our results.…”
mentioning
confidence: 99%
“…For voltages eV L = −eV R ≤ 2ω c [44] we have 12 ]+κ ↓ (2κ ↓ + Γ 02 ), and the rate Γ 12 = e −λ 2 λ 2 2 − λ 2 2 α Γ α n F (ω c −µ α )/2 for the transition from 1 to 2 photons in the cavity. Equation (4) agrees very well with the numerical calculations for k B T ≥ 0.1ω c , (cf.…”
mentioning
confidence: 99%
“…Circuits in which voltage biased Josephson junctions (JJ) are combined with microwave cavities provide an ideal platform for exploring a wide range of microwave photonics. All of the voltage energy associated with tunneling Cooper pairs must be transferred into photons and the properties of JJ-cavity systems can be tuned over a wide range either in-situ or by design, [1][2][3][4][5][6] . Furthermore, the energy transferred by tunneling Cooper pairs into microwave modes can be tracked by monitoring either the resulting dc current or the microwaves leaking out of the circuit 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the energy transferred by tunneling Cooper pairs into microwave modes can be tracked by monitoring either the resulting dc current or the microwaves leaking out of the circuit 1 . Recent experimental, [1][2][3][4][5][6] and theoretical work [7][8][9][10][11][12][13][14][15][16][17][18] has explored a wide range of ways in which JJ-cavity systems can be used to generate non-classical microwave states.…”
Section: Introductionmentioning
confidence: 99%